Tandem therapeutic plasma exchange and continuous kidney replacement therapy in a pediatric post-liver transplant patient: a case report - Fahlevi, Reza; Puspitasari, Henny Adriani; Hidayati, Eka Laksmi; Pardede, Sudung Oloan; Trihono, Partini Pudjiastuti; Puspaningtyas, Niken Wahyu; Oswari, Hanifah; Sanstiono, Sastiono (Indonesian Pediatric Society, 2025)
In critical condition, sometimes continuous kidney replacement therapy (CKRT) treatment should not be held while therapeutic plasma exchange (TPE) is needed. Simultaneous use of both modalities is defined as tandem therapy, available as an option.